1972
DOI: 10.1002/tera.1420060218
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age and congenital cleft lip and cleft palate

Abstract: In an analysis of 679 families no evidence was found of a diference in paternal or meternal ages between complete and incomplete forms of cleft lip, with or without cleft palate, or between familial and nonfamilial cases, It would appear that parental‐age effects for clefts of the lip or palate either do not exist or are so complex that their biological significance is likely to remain obscure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

1973
1973
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…9,10,39-49 The outcomes were not clearly defined in 29 studies. 14, [16][17][18]21,22,26,27,39,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Thirty-three studies did not define the exposure variables 7,8,14,15,18,22,23,34,40,41,[50][51][52][53][54][56][57][58][59][60][61][62][63][64][65][66]…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10,39-49 The outcomes were not clearly defined in 29 studies. 14, [16][17][18]21,22,26,27,39,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Thirty-three studies did not define the exposure variables 7,8,14,15,18,22,23,34,40,41,[50][51][52][53][54][56][57][58][59][60][61][62][63][64][65][66]…”
Section: Quality Assessmentmentioning
confidence: 99%
“…24,32,42,47,48,63,78,83 Twenty-three articles did not describe category boundaries when continuous variables were categorized. 7,14,19,22,23,26,27,34,40,[43][44][45]55,57,62,65,66,71,72,74,76,80,86 ORs were presented in 21 studies. 4,9,10,24,[29][30][31][32]36,37,42,44,47,48,73,[77][78][79]81,82,84 The relationship between paternal and/or maternal a...…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was Penrose who first showed that the association was due to advanced paternal age, but not maternal age or the child's birth order [16]. Paternal age at the birth of offspring has been associated with an increasing risk for several congenital disorders [17], including cleft lip and palate [18], syndactyly [19], situs inversus [20], hydrocephalus [21], Apert syndrome [22] and craniosynostosis [23]. Some other disorders associated with paternal age are childhood cancer [24,25], miscarriage [26], fetal death [27] and some autoimmune disorders [28].…”
Section: Introductionmentioning
confidence: 99%
“…Pour expliquer cette situation, certains auteurs ont fait l"hypothèse de l"implication de mutations de novo dont on sait qu"elles augmentent avec l"âge paternel. L"âge paternel avancé est non seulement considéré comme un facteur de risque du développement de la schizophrénie, mais a également été associé à de nombreux troubles neuro-développementaux (diminution des capacités intellectuelles et neuro-cognitives [1, 21,30,31], autisme [30]) ainsi qu"à d"autres pathologies (syndrome d"Apert, Progeria, achondroplasie [12,36,40], crâniosynostose [33], situs inversus [16], syndactylie [27], bec de lièvre [26,32], hydrocéphalie [32], cancer [10,43]). Une des explications étant la survenue de mutations au niveau des gamètes paternels responsables de l"apparition de cas sporadiques [4].…”
Section: I) Introductionunclassified